PERFORMANCE ASSESSMENT OF PUBLIC MANAGEMENT MUNICIPAL (Desenvolvimento em Questão, 2020)
This study aimed to develop a methodology based on multi-criteria analysis consists of performance indicators able to assess the performance of the municipalities regarding the social, economic and environmental aspects. Therefore, the methodological classification follows the following reasoning: applied research, exploratory and descriptive, bibliographical and documentary quantitative. The geographic divisions and the pilot test for application of the methodology was carried out in seventeen municipalities in the micro de Sousa, PB. The results demonstrate the applicability of PROMETHEE II model as a method for defining a rating scale - or index - the conditions of public administration, from the economic, social and environmental dimensions of municipalities brings significant results in this context. It is understood that the order obtained by the method emphasizes that there is inequality between the municipalities in the region in need of public strategies and policies aligned to each reality and context of the studied subject.
Keywords: Public Management. Performance indicators. Multi-criteria analysis.